Clinical researchAnalysis of demographic and clinical factors affecting the outcome of adioiodine therapy in patients with hyperthyroidism - Knapska-Kucharska, Małgorzata; Oszukowska, Lidia; Lewiński, Andrzej (Archives of Medical Science, 2010)
Introduction: The influence of demographic and clinical factors on the outcome of 131I therapy in hyperthyroid patients has been examined, based on a retrospective evaluation of results obtained in patients submitted to 131I treatment at the Department of Nuclear Medicine and Oncological Endocrinology, Medical University of Lodz (Province Hospital, Zgierz). The goal of the study was to analyse such factors as the age and sex of patients, disease duration, as well as the hormonal status before 131I application, which could have an influence on the effects of therapy with radioiodine 131I. Material and methods: The study involved 500 randomly selected patients with hyperthyroidism, treated with 131I radioiodine. The following 3 groups were defined: group 1 – patients with multinodular goitre (MNG), n = 200; group 2 – patients with a single autonomous nodule of the thyroid (AFTN), n = 100; group 3 – patients with Graves’ disease (GD), n = 200. The local ethics committee (in the Polish Mother’s Memorial Hospital – Research Institute, Lodz) approved the study. Results: The obtained results indicate that the efficacy of therapy with 131I applied in patients with MNG, AFTN and GD does not depend on either patient sex or patient age. The length of antithyroid treatment before 131I therapy onset does not appear to have any effect on the therapy outcome, and the baseline thyrotropin concentration seems to be significant only in the case of GD. Conclusions: The analysed demographic factors do not affect the outcome of 131I therapy in hyperthyroidism.